STUDIES ON THE LYSOZYME ACTIVITY IN THE MILK OF FEMALE DONKEYS ( E QUUS ASINUS) I N RELATION TO REPRODUCTIVE PHYSIOLOGY - A. S. Qureshi; H. Enbergs (Journal of Animal and Plant Sciences, 2012)
The lysozyme activity (LZA) in milk samples from 23 Jennies was measured on alternative days during the first 60 days postpartum with modified turbidimetric method. Progesterone profile in milk was determined by a comparative enzyme immunoassay. LZA ranged between 203 278 and 34 340 U/ml with an average of 93 023 + 28 128 U/ml. Lysozyme activities remained very high until the end of foal heat in all jennies. These values declined abruptly to a 25% lower level at the end of foal heat and followed a linear trend downward until 50th day p.p. and afterward, these values stabilized until the day 59 of the study. Jennies, who conceived in foal heat showed 15000 U/ml LZA significantly higher than those, which had not conceived in foal heat, until the end of foal heat. Lysozyme activity and progesterone content showed a significantly (P<0.001) negative correlation during foal heat and in subsequent heats. It is concluded that considerably higher lysozyme activity in milk can firstly be considered as a protective factor for the newborn and secondly, for the low susceptibility of jenny’s udder to infections. Moreover, it might play an important role in an intensive and rapid postpartal regeneration process of the uterus.
Keywords: Lysozyme activity; milk; reproduction; progesterone; donkey